Development and experimental investigation of Stirling-type pulse tube refrigerator (PTR) below 20 K; cold compressor and colder expander. (March 2017) - Park, Jiho; Jeong, Sangkwon; Cha, Jeongmin
Highlights: "Cold compressor and colder expander" concept is proposed. Stirling-type PTR with cold linear compressor is tested as a proof of the concept. Mass flow is generated by the compressor near 80 K with 85% compression efficiency. 18.7 K-no load temperature is recorded and 0.4 W-cooling power is measured at 20 K. Dynamic and thermal characteristics of the Stirling-type PTR are investigated. Abstract: This research paper focuses on the experimental investigation of the Stirling-type pulse tube refrigerator with cold compression concept. Due to this innovative feature, the pulse tube refrigerator can reach lower temperature effectively other typical single-stage Stirling-type pulse tube refrigerators. The experiment as a proof of concept is carried out to demonstrate the capability of the pulse tube refrigerator operating between 80 K and 20 K. The cold linear compressor, which is submerged in a liquid nitrogen bath, produces cold mass flow with the efficiency of 85% for all the frequencies. At the lowest temperature part of the pulse tube refrigerator, the no-load temperature of 18.7 K is recorded and the cooling power of 0.4 W is measured at 20 K. The experimental results are analyzed in dynamic and thermal aspects by using the numerical model. The model can well explain how much losses are distributed in the system.